Designing Autonomy at home. The ADA Project An Interdisciplinary Strategy for Adaptation of the Homes of Disabled Persons - LAURIA, ANTONIO (Studi e saggi, 2019)
Designing Autonomy at Home. The ADA Project. An Interdisciplinary Strategy for Adaptation of the Homes of Disabled Persons. Housing adaptations are one of the main tools for improving quality of life for people with severe disabilities and for their caregivers. They are also the main tool of the ADA Project, an action research that developed a strategy to tailor adaptations to the specific user needs and profiles. After an introduction to disability, accessibility and housing adaptations, the book describes the ADA Project's goals, stages and tools. It then focuses on the main scientific outcome of the Project: the ADA Assessment Model (AdAM), an interdisciplinary tool that analyses and assesses the functional and social profile of disabled persons and their relationship with the physical environment in which they live.